Classic fairy tales : the VCD that reads with me!. (Magnavision, 2005)
3 great stories such as The fairy ship, Cinderella, and the rooster, mouse and the red hen
Volume4: appropriate to ages two to and above
Keywords: The fairy ship; Cinderella; The rooster, mouse & the red hen